2021
DOI: 10.2495/sc210351
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on Cooling Demand of High-Rise Buildings in Hot/Humid Climates: A Review

Abstract: A significant amount of energy is consumed on cooling buildings in countries that experience hot/humid climates. The increasing demand for high-rise buildings, with their inherent air conditioning systems, adds extra requirements to electricity grids or local district cooling systems. Thus, this work is structured to identify the influencing factors of cooling energy demand in high-rise buildings that are geographically restricted to countries of these climates. The influence of the factor is quantified as its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Although there are some review articles that holistically address the factors that impact cooling demands, such as [13] and [14], they lack specific aspects. Chen et al [13] presented a review article about the internal and external influencing factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some review articles that holistically address the factors that impact cooling demands, such as [13] and [14], they lack specific aspects. Chen et al [13] presented a review article about the internal and external influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, reporting energy savings in terms of cooling demand and loads may be more significant and provide a more accurate picture of the true contribution of cooling demand to overall energy consumption. Also, Anaya et al [14] concluded that building envelope parameters are one of the most influencing factors on cooling loads, but they did not address the specific envelope parameters within cooling loads since the building envelope involves a considerable number of parameters that vary in their influence, such as glass characteristics, wall insulation, etc. Furthermore, their review is limited to high-rise buildings, in which a building exceeds 23 m only with no consideration of low-rise buildings.…”
Section: Introductionmentioning
confidence: 99%